The Efektifitas Edukasi Menggunakan Video Dan Booklet Pada Pengetahuan Dan Minat Kontrasepsi Postpartum Primigravida Di Puskesmas Pasundan - Anwar, Resti Refiani; Kalsum, Ummi; Siregar, Nursyahid (Politeknik Kementerian Kesehatan Banjarmasin, 2023)
Introduction: One of the efforts to accelerate the decline of maternal mortality is to ensure that every mother able to access contraception services, including postnatal contraception. The use of postnatal contraception will work if it is preceded by good counseling. The purpose of this study was to analyze the effectiveness of education using video and booklets on primigravida's postpartum contraception. Methods: This research’s type is a quasi-experimental research design with a non-equivalent control group. The study was conducted at the Pasundan Health Center Samarinda for 2 months. This study uses 2 intervention groups, videos and booklets with a sample of 18 respondents in each group. The sampling method used is purposive sampling. Result: The results of this study are that there are differences in knowledge and interest before and after being given an intervention with video (p-value 0.000), there is a difference in knowledge and interest before and after being given an intervention with booklet (p-value 0.000), and video is more effective than booklet to increase primigravida's postpartum contraception knowledge and interest (p = 0.001 and p = 0.008). Discussion: Media is one of the determining factors for the success of learning. The more senses used, the better the respondent's acceptance of health education messages or materials. Through video the learning process can be more interesting and fun (joyful learning) and become easier. Conclusion: Video education is more effective than booklet to increase knowledge and interest of primigravida. Keyword: Postpartum Contraception, Video, Booklet, Knowledge, Interests